2017
DOI: 10.1371/journal.pone.0171987
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with diabetic retinopathy among diabetic patients at Arbaminch General Hospital, Ethiopia: Cross sectional study

Abstract: BackgroundCurrently 93 million people are estimated as living with diabetic retinopathy worldwide. The prevalence and risk factors of diabetic retinopathy in developed countries have been well documented; but in Ethiopia, data on prevalence and associated factors of diabetic retinopathy is lacking.ObjectiveTo determine prevalence and factors associated with development of diabetic retinopathy among diabetic patients at Arbaminch General Hospital, Ethiopia.MethodCross-sectional study design with record review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
45
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 10 publications
(11 reference statements)
23
45
3
Order By: Relevance
“…This study identified that diabetic retinopathy was 51.3% prevalent among the enrolled type 2 diabetes patients. This finding is higher than the prevalence previously reported from Arbaminch [29] and Jimma [28] in Ethiopia and from other parts of the world [18][19][20][21][22][23][24]. However, our finding is lower than the one reported from Bahol in Iran [25].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…This study identified that diabetic retinopathy was 51.3% prevalent among the enrolled type 2 diabetes patients. This finding is higher than the prevalence previously reported from Arbaminch [29] and Jimma [28] in Ethiopia and from other parts of the world [18][19][20][21][22][23][24]. However, our finding is lower than the one reported from Bahol in Iran [25].…”
Section: Discussioncontrasting
confidence: 91%
“…The Diabetes Center of Tikur Anbessa Hospital is the major referral center for diabetes treatment in Ethiopia. The sample size was determined in advance based on the assumption of 95% confidence interval, 13% expected prevalence of diabetes retinopathy [29], and a 5% margin of error. The inclusion criteria were patients with type 2 diabetes according to the World Health Organization (WHO) criteria [30] and on stable anti-diabetic medication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study finding; DM patients who live with DM between 6-10 years and above 10 years were1.79 and 4.68 times more likely to develop diabetes complication respectively when compared with patients who had live with DM less than 5 years duration. Thisstudy was similar with study conducted in "Felegehiwot" referral hospital, Bahirdar, Arbaminch and Jimma[(15), (16)]. So, patients should be clinical managed properly by initiatingearly diagnose and treatment.…”
Section: Discussionsupporting
confidence: 86%
“…In this study diabetic patients who were with systolic hypertension (Systolic Blood Pressure greater than 140 mm hg) was also one independent factor that determines the development of DR among diabetic patients. Similar findings were also reported in China (15), Arbaminch (14), Korea (28) and in rural India (37).…”
Section: Providing Proper Health Information and Counseling On The Cosupporting
confidence: 86%